Perceived Oral Communication Skills and Classroom Participation of Introverted Senior High School Students in Communicative Language Teaching (CLT) Activities: Basis for a Quiet-Learner CLT Program - Oku, Emira (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the perceived oral communication skills and classroom participation of introverted senior high school students in Communicative Language Teaching (CLT) activities as basis for developing a Quiet-Learner CLT Program. Anchored on the Communicative Competence framework and the Willingness to Communicate model, the study focused on grammatical, sociolinguistic, discourse, and strategic competence, as well as students’ participation in role-playing, debates, group activities, pair work, and oral presentations. A quantitative descriptive-correlational research design was used. The respondents were 126 self-identified introverted senior high school students from a private university in Valenzuela City, Philippines. Data were gathered through a researcher-developed survey questionnaire that measured demographic profile, perceived oral communication skills, and perceived classroom participation in CLT activities. The instrument underwent expert validation and reliability testing. Data were analyzed using descriptive statistics, independent-samples t-test, one-way analysis of variance, Tukey post hoc test, and Pearson product-moment correlation. Findings showed that the respondents generally perceived themselves as good in grammatical competence and sociolinguistic competence, but only fair in discourse competence and strategic competence. In terms of CLT participation, students showed stronger engagement in pair work and group activities, while participation in role-playing and debates was relatively limited. Significant differences in oral communication skills were found when respondents were grouped according to selected demographic variables, particularly age, gender, academic strand, and socio-economic background. Participation in CLT activities also differed according to age, gender, and socio-economic background, while academic strand did not consistently influence participation patterns. Correlation results revealed that sociolinguistic, discourse, and strategic competence had significant positive relationships with participation in CLT activities, whereas grammatical competence showed weak and non-significant relationships with participation variables. These findings indicate that communicative, interactional, and strategy-based dimensions of language competence are more closely related to classroom participation than grammar alone. The study concluded that introverted learners need structured, supportive, and progressively scaffolded communicative activities that strengthen discourse and strategic competence while encouraging participation in low-pressure classroom settings. It recommended the implementation and further evaluation of the proposed Quiet-Learner CLT Program to support inclusive English language instruction. The study aligns most directly with SDG 4 – Quality Education and SDG 10 – Reduced Inequalities by promoting inclusive communicative learning opportunities for quiet and introverted learners. Its sustainability impact lies in strengthening educational and institutional practices that support learner diversity, equitable classroom participation, and evidence-based language teaching.